An Evaluation of the Effects of Various Fertilizer Applications on the Growth, Nutritive Value, and Quality of Barley Sprouts Produced in Hydroponics - Hidir Gümüs; Eren Kuter; Umair Ahsan; Derya Merve Karagöz; Elif Zeynep Oguz; Esra Çagan Ulusan (Journal of Animal and Plant Sciences, 2024)
We examined the effects of various fertilizing techniques on the growth, nutritive value, and quality of barley fodder produced by a hydroponic chamber in this study. Four experimental groups were designed as control (with no fertilizer); S (seeds only treated with fertilizer before planting); S1 (sprouts only treated with fertilizer after 4 d of planting), and S2 (both seeds before planting and sprouts after 4 d of planting treated with fertilizer). The highest shoot height, root length, and fresh and dry forage weights were seen in S2-group. Different fertilizer applications increased the dry matter content and decreased the dry matter loss of sprouts compared to the control. The crude protein, ether extract, ash, in vitro dry matter digestibility, crude fiber, acid detergent fiber, and crude fiber contents of sprouts were greater in treatment groups compared to the control. After harvesting, lower neutral and acid detergent fiber, nitrogen-free extract, and hemicellulose were detected in the fertilized groups than the control. The relative feed value and relative feed quality in S2-fodder were the highest among all groups. In conclusion, the application of fertilizer to both seed and sprout may improve the growth, nutrient content, and quality values of barley sprouts.
Keywords: Green sprout yield; nutritive value; hydroponic system